Catalase protects Aedes aegypti from oxidative stress and increases midgut infection prevalence of Dengue but not Zika. - José Henrique M Oliveira; Octávio A C Talyuli; Renata L S Goncalves; Gabriela Oliveira Paiva-Silva; Marcos Henrique F Sorgine; Patricia Hessab Alvarenga; Pedro L Oliveira (Public Library of Science (PLoS), 2017)
BACKGROUND:Digestion of blood in the midgut of Aedes aegypti results in the release of pro-oxidant molecules that can be toxic to the mosquito. We hypothesized that after a blood meal, the antioxidant capacity of the midgut is increased to protect cells against oxidative stress. Concomitantly, pathogens present in the blood ingested by mosquitoes, such as the arboviruses Dengue and Zika, also have to overcome the same oxidative challenge, and the antioxidant program induced by the insect is likely to influence infection status of the mosquito and its vectorial competence. METHODOLOGY/PRINCIPAL FINDINGS:We found that blood-induced catalase mRNA and activity in the midgut peaked 24 h after feeding and returned to basal levels after the completion of digestion. RNAi-mediated silencing of catalase (AAEL013407-RB) reduced enzyme activity in the midgut epithelia, increased H2O2 leakage and decreased fecundity and lifespan when mosquitoes were fed H2O2. When infected with Dengue 4 and Zika virus, catalase-silenced mosquitoes showed no alteration in infection intensity (number of plaque forming units/midgut) 7 days after the infectious meal. However, catalase knockdown reduced Dengue 4, but not Zika, infection prevalence (percent of infected midguts). CONCLUSION/SIGNIFICANCE:Here, we showed that blood ingestion triggers an antioxidant response in the midgut through the induction of catalase. This protection facilitates the establishment of Dengue virus in the midgut. Importantly, this mechanism appears to be specific for Dengue because catalase silencing did not change Zika virus prevalence. In summary, our data suggest that redox balance in the midgut modulates mosquito vectorial competence to arboviral infections.